Antibiotic therapy as an adjunct to scaling and root planing in smokers: a systematic review and meta-analysis - Assem, Naida Zanini; Alves, Márcio Luiz Ferro; Lopes, Alessandra Barreto; Gualberto, Erivan Clementino; Garcia, Valdir Gouveia [UNESP]; Theodoro, Letícia Helena [UNESP] (FapUNIFESP (SciELO), 2017)
The aim of this study was to perform a systematic review and meta-analysis to examine the effect of systemic antibiotics in the periodontal treatment of smokers. The selection criteria were as follows: controlled randomized clinical trials; studies published in English; studies with smoker patients diagnosed with chronic periodontitis; patients without systemic diseases; studies that used systemic antibiotic therapy associated with periodontal treatment; studies that presented results for the test and control groups and assessments of clinical periodontal parameters, such as probing depth (PD), bleeding on probing (BOP), and clinical attachment level (CAL). The differences in average weights were calculated with a confidence interval (CI) of 95% for PD reduction, CAL gain and BOP. The means of the periodontal clinical parameters were compared between the baseline and post-treatment periods between the test groups and the control groups. The heterogeneity was assessed using the Cochran Q test (Q (df = 3), α = 5%). A total of 67 articles were found, and after the selection process, three randomized controlled trials were included in the meta-analysis. The results indicate that SRP associated with systemic antibiotics promoted additional benefits when compared to SRP alone, with a greater reduction of PD (p = 0.0359, CI = -0.42, -0.01) and a gain of CAL (p = 0.0161, CI = -0.39, -0.04). There was a modest PD reduction (PD, DM -0.21) and a modest CAL gain (CAL, DM -0.22). The results of our meta-analysis reveal the clinical benefits of systemic antibiotics as an adjunct to the non-surgical periodontal treatment of smokers. These clinical improvements, although statistically significant, appeared to be of little clinical relevance.